Evidences of Bedrock Forcing on Glacier Morphodynamics: A Case Study in Italian Alps - Dematteis, Niccolò; Giordan, Daniele; Perret, Paolo; Grab, Melchior; Maurer, Hansruedi; Troilo, Fabrizio (Frontiers in Earth Science, 2022)
In mountain glaciers, the influence of bedrock geometry on glacier surface morphology is often assumed; quantitative evidence, however, is rare. In our research, we measured the ice thickness of the Planpincieux Glacier (North-west Italy) and detected the bedrock topography using ground-penetrating radar. Additionally, we investigated the glacier surface morphology using structure from motion and the glacier kinematics using digital image correlation of terrestrial images. A digital terrain analysis showed evidence of recurrent crevasses whose position corresponded to bedrock steps. On average, since 2014, their positions varied between 6 and 14 m and were 40 ± 8 m downstream of the bedrock steps. Bedrock and glacier topography presented out-of-phase correlated undulations that approximately fit a sinusoidal function of different amplitude. Moreover, we show the morphological evolution of an unstable sector whose thickness at the end of the ablation seasons has remained approximately constant since 2014. Contrarily, the ice melting during the 2020 ablation season caused a volume loss of >30%. Since, in general, the damages provoked by a potential ice avalanche depend primarily on the involved volume, this finding demonstrates that frequent morphology monitoring is essential for correct glacial hazard assessment.